2017
DOI: 10.1007/978-3-319-65151-4_31
|View full text |Cite
|
Sign up to set email alerts
|

Managing Business Process Variability Through Process Mining and Semantic Reasoning: An Application in Healthcare

Abstract: Managing process variability enable the process model adaptability according changes in the application environment. In the healthcare area, flexibility is essential to provide a quality treatment because, even patients with the same diagnostic, may follow different paths and suffer different proceedings. Besides, there are many aspects to be considered for the selection of a path, as patient's symptoms, and clinical guidelines, among others. In this context, this research presents a framework for the manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For this reason, some authors refer to this type of comparison as a conformance checking or conformance analysis [ 6 , 17 , 19 ]. These studies [ 20 , 21 , 22 ] often include and overlap with a consistent number of papers that aim to identify variants and similarities of pathways within a cohort of patients with similar health conditions [ 23 , 24 , 25 , 26 ].…”
Section: Related Workmentioning
confidence: 99%
“…For this reason, some authors refer to this type of comparison as a conformance checking or conformance analysis [ 6 , 17 , 19 ]. These studies [ 20 , 21 , 22 ] often include and overlap with a consistent number of papers that aim to identify variants and similarities of pathways within a cohort of patients with similar health conditions [ 23 , 24 , 25 , 26 ].…”
Section: Related Workmentioning
confidence: 99%
“…Health processes are mostly classified as ad hoc processes, in the sense that the same treatment can follow different paths by virtue of the patient's response, but also of the discretion of doctors who have the power to deviate from the guidelines on the basis of their knowledge and experience to address specific patient situations (Detro et al, 2017). In this context, it is of crucial importance to have techniques capable of discriminating different behaviors in the same process so that the analyst can study them separately.…”
Section: Variants Analysismentioning
confidence: 99%
“…The ontology, implemented in the OWL description logic, is used for matching the data of a patient with that of other healthy patients, while conformance checking algorithms are used to compare process model of a patient with the process model of healthy patients. Detro et al (2017) proposed a semantic PM framework for selecting the appropriate process variant according with the patient's symptoms by means of ontologies based on known expertise.…”
Section: Event Log Quality Improvementmentioning
confidence: 99%
“…Technical limitations were identified in 13 papers [28], [23], [51], [46], [41], [27], [44], [45], [32], [33], [37], [48], [55] including limitations in computer processing power, memory usage, bias associated with the mining algorithm, and simplifying the control flow due to computational complexity. There were no studies which reported limitation of team composition, however, 14 studies reported that they had involved clinician(s) to help the team with analysis or verification of results [28], [23], [46], [41], [54], [30], [27], [32], [33], [48], [55], [49], [50], [42].…”
Section: Limitations and Future Workmentioning
confidence: 99%